Analysis Of The Effectiveness Of Distribution Of Zakat Funds By The Baitul Maal PLN Foundation (YBM PLN) - Rahmad Ridho Zeen; Nurhayati Nurhayati (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
It is obligatory for everyone who is economically capable to give zakat, not only as a form of sympathy for someone's situation but also to protect them from famine or other disasters. Zakat is one of the most important factors in eradicating poverty which is a source of disaster for both individuals and society. therefore in Islam it is obligatory to give zakat to people who are able in accordance with the word of Allah SWT. "Indeed, zakat is only for the noeedy, poor people, zakat administrators, converts who are persuaded by their hearts, to (liberate ) slaves, people who are in debt, for the path of Allah and for those who are on a journey, as a decree required by Allah, and Allah is All-Knowing, All-Wise." (At-Taubah: 60). In this research, the effectiveness of distributing zakat funds at YBM Pln will be discussed.